Scooby-Doo! and the masked magician - Gelsey, James (New York : Scholastic, 2001)
The Mystery, Inc. gang is visiting the Magic Palace, a place where magicians can make twelve-course dinners appear--yum! But then the famous masked magician makes a priceless diamond necklace
A Little Apple paperback.
At head of title: Cartoon Network.
540
Accelerated Reader AR
Keywords: Scooby-Doo -- (Fictitious character) -- Juvenile fiction; Mystery and detective stories; Dogs -- Juvenile fiction